Piotr Tłuk ze Strykowa h. Łazęka (zm. 1468) – rycerz, polityk i gospodarz - Łukasz Ćwikła (Meluzyna: dawna literatura i kultura)
The aim of this article is to present the figure of Piotr from Stryków, Łazęka coat of arms. He came from Stryków, located in the Łęczyca Land (Brzeziny County), which was the seat of the Łazęka family. After the death of his brothers, he became the sole administrator of the family estate. The text shows various aspects of the title character’s activities. The main attention was focused on his property and investment activities. In addition, his knighthood card and participation in the Battle of Chojnice (1454) were signaled, as well as his political activities on the national and local level. Piotr had large financial resources at his disposal, because in the light of the current state of research, the transactions he conducted (until the mid-15th century) slightly exceeded the amount of 5,000 grzywnas. One of his economic strategies was to pledge land with the possibility of perpetual takeover.